2010
DOI: 10.1016/j.avb.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of personal, familial, and abuse-specific factors with outcome following childhood sexual abuse

Abstract: of personal, familial, and abuse-specific factors with outcome following childhood sexual abuse" (2010). Faculty Publications, Department of Psychology. 550. http://digitalcommons.unl.edu/psychfacpub/550 C hildhood sexual abuse (CSA) has become one of the most widely researched areas in child psychology in recent years. The public has also been made more aware of CSA and possible effects of sexual abuse through efforts from advocacy groups as well as the use of research data in recent political legislation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 61 publications
1
42
1
3
Order By: Relevance
“…Our results showed that the more distant the relationship between the child and the perpetrator, the more likely the child is to present externalizing problems. This result was unexpected and contrary to what is reported in the literature (Yancey & Hansen, 2010). It is important to remain critical about this result, considering the distribution of the variable (only 2% of the sample had been abused by a stranger and 73% by a family member).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results showed that the more distant the relationship between the child and the perpetrator, the more likely the child is to present externalizing problems. This result was unexpected and contrary to what is reported in the literature (Yancey & Hansen, 2010). It is important to remain critical about this result, considering the distribution of the variable (only 2% of the sample had been abused by a stranger and 73% by a family member).…”
Section: Discussioncontrasting
confidence: 56%
“…One hypothesis could be that the more distant perpetrators (e.g. stranger) are more likely to use force to perpetrate the acts of abuse (Fischer & McDonald, 1998) and that this violence is associated with greater externalizing symptoms (Yancey & Hansen, 2010). However, the use of force did not correlate with any of the studied variables.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…! family breakdown (Alaggia, 2004;Staller, & Nelson-Gardell, 2005); this was especially true when the abuser was a family member (Yancey, & Hansen, 2010).…”
Section: ! !mentioning
confidence: 99%
“…Most importantly, this elucidated the unique effect of the father-child relationship. Past studies had delineated the influence of the mother-child relationship (Cyr et al 2003;Plummer and Eastin 2007;Rakow et al 2011) or the global parental relationship (Bolen and Lamb 2007;Tremblay et al 1999;Yancey and Hansen 2010) on children's outcomes. Yet, until now few studies had more specifically explored the possible influence of the father-child relationship on children's recovery following disclosure of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%